Therapeutically relevant aspects in bone repair and regeneration. Issue 10 (December 2015) - Perez, Roman A.; Seo, Seog-Jin; Won, Jong-Eun; Lee, Eun-Jung; Jang, Jun-Hyeog; Knowles, Jonathan C.; Kim, Hae-Won
Abstract : Over the past few years, attention has been focused on the therapeutic roles in designing bone scaffolds for successful repair and regeneration. Indeed, biologically dynamic events in the bone healing process involve many of the molecules and cells adherent to the scaffold. Recent bone scaffolds have been designed considering intrinsic chemical and physical factors and exogenous/extrinsic cues that induce bone regeneration. Here, we attempt to topically review the current trends and to suggest featured strategies for the design of therapeutically relevant bone scaffolds taking into account recent studies and applications.